Prognostic implications of cholesterol chrystals at ACS causing culprit lesions, insights from the translational OPTICO-ACS study program. (14th October 2021) - Nelles, G; Abdelwahed, Y; Seppelt, C; Meteva, D; Staehli, B; Kraenkel, N; Steiner, J; Skurk, C; Riedel, M; Sieronski, L; Haghikia, A; Sinning, D; et al.
Abstract: Aims: Cholesterol chrystals (CC) represent a feature of advanced plaque remodeling. Optical coherence tomography (OCT) allows for detailed morphological assessment of the culprit lesion, including the presence of CCs, in vivo. Since CCs have been identified as prognostically relevant plaque feature in coronary artery disease (CAD), the present analysis aims to further characterize their impact on adverse cardiovascular outcome in a large cohort of patients, presenting with acute coronary syndrome (ACS). Methods: Within the translational OPTICO-ACS study program, 371 consecutive ACS-patients were included into the final analysis. OCT-characteristics, including the presence of CCs, were assessed by a standardized CoreLab analysis following universal consensus standards for OCT-derived plaque features. All patients were followed up for 12 months after the index event and major adverse cardiac events (MACE) consisting of death, myocardial infarction, target vessel revascularization plus re-hospitalization due to unstable or progressive angina pectoris were documented. Results: 215 patients (58.1%) presented with cholesterol chrystals (CCs) at the culprit lesion. Plaque rupture (RFC-ACS) represented the primary ACS-causing pathophysiology (75.3%) in those patients. Further, the presence of CCs was associated with other high-risk features within the culprit lesion, i.e. the presence of thin cap fibroatheroma (77.7% vs. 63.2%; p<0.05), plaque calcification (80.5% vs. 67.1; p<0.01) and microchannels (80.1% vs. 70.1; p<0.05) as well as an increased area stenosis (0.77 vs. 0.73 mm 2 ; p<0.01) and a greater maximum lipid arc (282.8 vs. 242.6°; p<0.01) as compared to culprit lesions free of CCs. Of note, there was a strong association among the occurrence of macrophages within the plaque and cholesterol crystals. Finally, and most importantly MACE during 12 months follow-up, consisting of cardiac death, myocardial infarction, target vessel revascularization and re-hospitalization due to progressive or unstable angina pectoris, occurred with nearly twice the frequency in CC-patients (20.3% vs. 10.6%; p<0.01) as compared to patients without CCs at the culprit site. Conclusion: The present analysis introduces cholesterol chrystals as a novel prognostically relevant high-risk plaque feature allowing individual risk stratification for patients after ACS. FUNDunding Acknowledgement: Type of funding sources: None.